Performance-based Seismic Analysis of Rocking Masonry Façades Using Non-linear Kinematics with Frictional Resistances: A Case Study. Issue 9 (2nd September 2021) - Casapulla, Claudia; Maione, Alessandra; Argiento, Luca Umberto
ABSTRACT: In this paper the seismic assessment of rocking masonry walls is evaluated through the displacement-based approach. In particular, a case study is selected to analyse the rocking failure mechanism of the façade of an ancient masonry church, damaged during the 2016–17 Central Italy seismic sequence. For this purpose, a non-linear kinematic analysis is developed to define the load factor at the activation of the failure mechanism and its evolution until collapse, at large displacements. An advanced macro-block model is adopted to take into account the stabilising contribution of frictional resistances exerted by the interlocked walls. The seismic input is described through acceleration-displacement response spectra (ADRS), provided both by seismic codes and selected real accelerograms, and the seismic analysis is addressed according to the capacity spectrum method (CSM), in the form incorporated into the latest Commentary to the Italian Technical Standard for Construction (CNTC19). The capacity is compared with the seismic demand through safety indexes, in terms of both forces and displacements, and the relevant influence of the frictional resistances on increasing the capacity is discussed. Incremental static analysis (ISA) curves are presented as another approach useful to highlight the relation between the peak ground acceleration (PGA) and the displacement demand.